Vibrational Properties of Doped P3HT Chains in Solution: Insight into the Doping Mechanism from Infrared IRAV and Raman RaAV Bands - Kaiyue Hu; Sara Doti; Luigi Brambilla; Mirella Del Zoppo; Chiara Castiglioni; Giuseppe Zerbi (Molecules)
Chemical doping is a well-established technique for increasing the electrical conductivity of polyconjugated polymers, and its effectiveness can be assessed through IR spectroscopy, thanks to the rise of the so-called IRAVs (infrared activated vibrations), which prove the formation of polarons on the polymer chain. While the mechanism of the IRAVs activation has been widely explored in the past, several peculiar features remain unclear. Changes in the Raman spectrum of doped polymers (RaAV, Raman activated vibrations) are widely used as well for monitoring the doping process, but the interpretation is often limited to purely empirical correlations. By means of an experimental campaign on doped regio-regular poly(3-hexylthiophene-2,5-diyl) (P3HT) samples in chloroform solution and on the solid samples cast from the same solutions, this paper presents for the first time a thorough comparative analysis of IRAVs and RaAVs, aiming at a unified description of the structure of doped P3HT. In particular, we will discuss the effect of the doping level on the vibrational features of the polymer and the dopant so that spectroscopic markers can be found to be used in the identification of the presence of ICT (integer charge transfer) complexes in different doping regimes. This study demonstrates that combining IR, Raman, and UV-Vis-NIR spectroscopies provides a powerful, complementary set of tools to diagnose not only the doping level but also the detailed molecular and supramolecular structure of the doped P3HT, useful for the development of structure/properties relationships in the perspective of the optimization of the charge transport performances.